Moho Depths of Antarctica: Comparison of Seismic, Gravity, and Isostatic Results. (28th March 2019) - Pappa, F.; Ebbing, J.; Ferraccioli, F.
Abstract: The lithospheric structure of Antarctica is still underexplored. Moho depth estimate studies are in disagreement by more than 10 km in several regions, including, for example, the hinterland of the Transantarctic Mountains. Taking account the sparseness of seismological stations and the nonuniqueness of potential field methods, inversions of Moho depth are performed here based on satellite gravity data in combination with currently available seismically constrained Moho depth estimates. Our results confirm that a lower density contrast at the Moho is present under East Antarctica than beneath West Antarctica. A comparison between the Moho depth derived from our inversion and an Airy‐isostatic Moho model also reveals a spatially variable buoyancy contribution from the lithospheric mantle beneath contrasting sectors of East Antarctica. Finally, to test the plausibility of different Moho depths scenarios for the Transantarctic Mountains‐Wilkes Subglacial Basin system, we present 2‐D lithospheric models along the Trans‐Antarctic Mountain Seismic Experiment/Gamburtsev Mountain Seismic experiment seismic profile. Our models show that if a moderately depleted lithospheric mantle of inferred Proterozoic age underlies the region, then a shallower Moho is more likely beneath the Wilkes Subglacial Basin. If however, refertilization processes occurred in the upper mantle, for example, in response to Ross‐age subduction, then a deeper Moho scenario is preferred. We conclude that 3‐D lithospheric modeling, coupled with the availability of new seismic information in the hinterland of the Transantarctic Mountains, is required to help resolve this controversy, thereby also reducing the ambiguities in geothermal heat flux estimation beneath this key part of the East Antarctic Ice Sheet. Plain Language Summary: Antarctica is a vast and remote continent that is mostly buried beneath the largest ice sheets left on Earth. Consequently, its deep structure is still poorly known, despite its importance as the cradle on which the overlying ice sheets flow. By studying anomalies in the gravitational field of the Earth as measured by satellites and using independent constraints derived by measuring seismic wave travel times from distant earthquakes, we investigate the variations in the depth of the boundary between Earth's crust and mantle (known as the Moho) beneath Antarctica. Our models confirm that the older cratonic regions of East Antarctica have generally deeper Moho compared to the younger geological provinces of West Antarctica. They also highlight that large regions of East Antarctica may exhibit contrasting mantle characteristics, and this lends further weight to recent geological and geophysical studies, indicating that East Antarctica is composed of different Precambrian provinces. In our study we re‐evaluated in particular two Moho depth scenarios derived from previous seismic studies for the hinterland of the Transantarctic Mountains, where the enigmatic Wilkes Subglacial Basin lies. We show that if an old Precambrian mantle is assumed, then a thin crust scenario beneath the basin is more likely, but if the mantle has been in part modified by more recent (ca. 500 Ma old) subduction, then a thicker crust scenario would become more viable. Overall, our study calls for combining gravity, seismological, and petrological modeling for enhanced Antarctic lithosphere and isostatic studies. Key Points: Moho depth beneath Antarctica is estimated from inversion of satellite gravity and seismological data Results indicate spatially variable buoyancy contribution of the upper mantle in both West and East Antarctica Regional 2‐D lithospheric modeling demonstrates the need for further seismological constraints in particular in interior East Antarctica